THE USE OF DIGITAL STORYTELLING IN LEARNING LISTENING BASED ON STUDENTS’ COMPREHENSION IN EFL CLASS - Jordan Alan; Nurul Aini; Ninda Ma'uunatul (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
Abstract: The motivation behind this study was to decide the reaction of EFL students to the use of Digital Storytelling in learning Listening based on understanding. The researcher collected the sample for this study administered 30 participants from six-semester EFL students of English Department. This research is included in the quantitative approach and the research design used is quantitative survey research. The research instrument is a questionnaire. Judging from the survey results, the responses of EFL students to the use of Digital Storytelling in Listening Skills learning were positive and the final results of the questionnaire which consisted of 10 total items showed a pleasant classification. The findings of this study shows that 30% strongly agree to the statement “Moving pictures in digital storytelling help you understand the story being told”. Meanwhile, there were 0% participant chose strongly disagree. This study intends to examine EFL students' responses to the use of Digital Storytelling in learning Listening skills. As well as to investigate how EFL students feel about using Digital Storytelling. The data shows that Digital Storytelling is an effective language-learning media. Keywords: Digital Storytelling, EFL, Learning, Listening Skills.